Decision Model of Repair Contract Selection and Spares Provisioning - Sasivimonlux, Kitti; Mongkolthep, Wiroj (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this academic article is to take the statistic theory and the decision theory for applying in decision model presentation of repair contract selection and spares provisioning by using utility function as the rule of decision. The model of repair contract selection is as following equation and the repair contract selection given maximum E[U(Ti, C)] value will be selected and the model of spares provisioning is as following equation and the spares provisioning given maximum U(,C) value will be selected as well.